Curcuma xanthorrhiza Rhizome Extract Induces Apoptosis in HONE-1 Nasopharyngeal Cancer Cells Through Bid - Ranggaini, Dewi; Sandra, Ferry; Halim, Johni; Ichwan, Solachuddin Jauhari Arief; Djamil, Melanie Sadono (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Curcuma xanthorrhiza rhizomes have been demonstrated to have anticancer properties toward various types of cancer cells. The effect of C. xanthorrhiza rhizome extract (CXRE) on nasopharyngeal cancer (NPC) cells, including HONE-1 cell line has not been elucidated yet. Therefore, the effect of CXRE on the apoptosis of HONE-1 cells and its possible underlying mechanism are necessary to be explored.METHODS: C. xanthorrhiza rhizomes were minced, dried, extracted with distilled ethanol, filtered, and evaporated to produce CXRE. HONE-1 cells were seeded, starved, and treated with dimethyl sulfoxide (DMSO), Doxorubicin, or various concentrations of CXRE. Treated HONE-1 cells were stained with 4',6'-diamidino-2-phenylindole (DAPI) and the number of viable cells was counted. HONE-1 cells were also collected, lysed, and further processed for immunoblotting analysis to measure Bid activity.RESULTS: The number of viable HONE-1 cells decreased in concentration- and time-dependent manner. The number of viable cells in 50 and 250 μg/mL CXRE-treated groups were significantly lower compared with that in the DMSO-treated group after 24 h. At 48 h incubation period, the number of viable cells in 10, 50 and 250 μg/mL CXRE-treated groups were significantly lower compared with that in the DMSO-treated group. The number of viable cells in 250 μg/mL CXRE-treatment group was not significantly different compared with that in the Doxorubicin-treated group after 48 h. Bid expression levels in CXRE-treated groups were lower compared with that in the DMSO-treated group.CONCLUSION: CXRE could induce apoptosis via Bid activation, hence reducing the viability of HONE-1 cells.KEYWORDS: Curcuma xanthorrhiza, nasopharyngeal cancer, HONE-1 cells, apoptosis, Bid